Edukasi Hukum Dan Kesadaran Psikologis KDRT Melalui Penyuluhan Interaktif Bagi Masyarakat Cawas Klaten - Muhammad Kurniawan Budi Wibowo; Aditya Fajri Kurnia Pradana; Muhammad Luthfi Dwi Pramukti (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This article discusses the community’s low legal awareness of domestic violence, especially in rural areas such as Cawas Village, which has led to minimal reporting and protection of victims. The purpose of this article is to improve the community’s legal understanding of domestic violence and encourage active participation in efforts to prevent and report domestic violence. The method used is a participatory approach through interactive legal counselling and pro bono advocacy, with empirical studies based on direct observation in the field and interviews with residents. Shows that interactive counselling succeeded in increasing residents’ legal literacy related to domestic violence, especially in understanding forms of violence and victims’ rights. Participants showed positive responses, but challenges still arise in the form of fear of reporting and social stigma against victims. The involvement of community leaders proved important in creating safe spaces and supporting legal protection at the village level. Therefore, sustainable and community-based legal education is essential to build a just and gender-equitable legal culture